Customers’ Satisfaction and Causes of Satisfaction in Emergency Room Srinagarind Hospital, 2014 - Mitsungnern, Thapanawong; Kotruchin, Praew; Phu-ngoen, Pariwat; Tacha-a-tik, Panor; Prasanson, Tipawan; Sumritrin, Sumana; Lathum, Kalayarat (Srinagarind Medical Journal, 2016)
Background and Objectives: The patient’s satisfaction is an important indicatoro of Emergency Room (ER) quality that consistent with Hospital and Healthcare Standard 2006 of The Institute of Hospital Quality Improvement & Accreditation, THAILAND. From past studies, we found many modifiable factors influencing satisfaction including 5 components e.g. personnel, time, systems, patient characters and place. This study aimed to find levels and causes of ER customers’ satisfaction. Leading to service’s quality improvement that match the customers’ need. Materials and Methods: We conducted a descriptive study in customers, who came to ER, Srinagarind hospital during June to November 2014 by simple random. Customers answered one self-questionnaire per one visit. There were two methods in this questionnaires to find level of satisfaction including Likert and simple descriptive scale. Data were analyzed by descriptive statistics e.g. range, average, ratio, and percentage. Results : Overall, there were 101 customers answered questionnaires, age range was between 10-81 years, mean age was 35.41 years. Sixty nine cases were females (68.3%). Seventy five were patients who answered by themselves (74.26%). We evaluated levels of customers’ satisfaction by two methods (100 cases in Likert method, and 88 cases in simple descriptive method). The mean of overall satisfaction got 3.68 out of 5 by Likert method, as similar as 7.72 out of 10by simple descriptive method. The most satisfaction was intention of healthcare personnel (33 cases) On the other hand, the most unsatisfaction was service time (30 cases). Conclusion : Customers’satisfaction in ER was minimal to moderate. The most satisfactory factor was intention of healthcare personnel while the most unsatisfactory factor was service time. The result will lead to quality improvement of ER and future research.